2011
DOI: 10.1007/s00427-011-0367-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of the zebrafish orthologue of Klotho

Abstract: Klotho is an aging suppressor gene. In mice, loss of Klotho function causes accelerated aging while increased Klotho expression increases longevity. This study aimed to identify and characterize the orthologue of Klotho in zebrafish, a powerful model organism for the investigation of development and human disease. Zebrafish klotho was identified by a bioinformatics approach, and cloning and sequencing of klotho cDNA confirmed the in silico analysis. The zebrafish Klotho protein has a structure similar to human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
5
7
0
Order By: Relevance
“…In a recently published study that used RT-PCR and qRT-PCR methods, αklotho expression could be detected in zebrafish embryos as early as 5 hpf [22]. We show here that zebrafish αklotho could be detected in 24 hpf embryos by whole-mount in situ hybridization (Figure 5A).…”
Section: αKlotho Expressionsupporting
confidence: 65%
“…In a recently published study that used RT-PCR and qRT-PCR methods, αklotho expression could be detected in zebrafish embryos as early as 5 hpf [22]. We show here that zebrafish αklotho could be detected in 24 hpf embryos by whole-mount in situ hybridization (Figure 5A).…”
Section: αKlotho Expressionsupporting
confidence: 65%
“…2). These results agree with previous findings in zebrafish showing that αklotho transcripts were evident during early embryonic stages and gradually increased as development proceeded (Sugano and Lardelli 2011). Also in mouse, α Klotho immunoreactivity was initially observed at embryonic day 16 followed by an apparent induction after birth (Song et al 2014).…”
Section: Resultssupporting
confidence: 93%
“…1 a). In mammals, N-terminal signal sequences have been described for both Klotho paralogs (Kuro-o et al 1997 ; Ito et al 2000 ) which is apparently lacking in zebrafish α Klotho (Sugano and Lardelli 2011 ) and also in the two Klotho paralogs in the nematode Caenorhabditis elegans (Château et al 2010 ). Using the protein prediction resource InterProScan (Finn et al 2017 ), we found a strong putative signal sequence for both killifish orthologs α Klotho (AA 1–18) and βKlotho (AA 1–25).…”
Section: Resultsmentioning
confidence: 99%
“…More details on the mouse Klotho gene and the identification of the human (96% homology) as well as the rat Klotho gene were reported 1 year later ; two distinct transcripts encoding membrane and secreted Klotho protein were characterized. Klotho has been identified not only in the zebrafish, Danio rerio, but two Klotho-like genes, klo1 and klo2, have also been identified in the nematode Caenorhabditis elegans (Polanska et al 2011, Sugano & Lardelli 2011, Mangos et al 2012. The corresponding KLO1 and KLO2 proteins lack a transmembrane domain.…”
Section: Klotho a Transmembrane Co-receptor And A Multifunctional Humentioning
confidence: 99%